Análise de redações nota mil do ENEM 2022: a prática do texto dissertativo-argumentativo - Santos, Rafaele Rocha dos (2023)
The argumentative-expository writing is a skill that plays a central role in the National High School Exam (ENEM) 2022. Developing this writing skill constitutes an enhancement of communication abilities. In this context, our research aims to conduct an exploratory analysis of essays that received the highest scores in the National High School Exam (ENEM) in the year 2022, with a special focus on the analysis of argumentative-expository texts. The goal is to identify how the patterns, characteristics, strategies, elements, and competencies required by ENEM regulations are present in the essays. Our research is bibliographical and documentary analysis, with a qualitative, exploratory approach using a comparative method, where four essays from different states in the Northeast region were collected and analyzed. In conducting the analyses, the results emphasized the importance of students demonstrating balance and proficiency in utilizing both structural elements and content to achieve the maximum score in the ENEM essay, as it serves as an essential foundation for the improvement of argumentative writing.